Significance of Forecast Precision: The Importance of Investors’ Expectations - Rupar, Kathy (Contemporary Accounting Research, 2017)
Abstract I investigate whether the alignment between individual investors’ expectations about forecast precision and actual forecast precision affects their estimates of firm value, and whether this relationship is mediated by individual investors’ perceptions of management credibility and future firm growth. Experimental results confirm that when expected and actual forecast precision align, individual investors estimate higher firm stock prices than when expected and actual forecast precision do not align. I also provide evidence of a mediation path through which the misalignment between expected and actual forecast precision affects individual investors’ perceptions of management credibility, future firm growth, and estimates of firm stock price. My findings help reconcile inconsistencies in prior earnings forecast literature and inform managers and researchers about strategies that lead to higher perceptions of management credibility and firm value.